Betawi Speech Shift in Internal Family Communication - Iskandarsyah Siregar; Samsur Rijal Yahaya (Budapest International Research and Critics University, 2022)
Language is a tool to convey messages from articulators to auditors. Thus, the core of the language process is how messages can be conveyed effectively and efficiently using the way that is considered the best. Language always experiences development and change. These developments and changes occur due to various factors, such as social, economic and cultural dynamics. Using two languages side by side may cause language distortion in its implementation. The problem that emphasizes is the shifting of the Betawi dialect in the family domain, especially the Betawi descendants who live in Jakarta. This study aims to determine the form of shifting the Betawi dialect. Data was provided using questionnaires, and random interviews aimed explicitly at some Betawi communities in the family domain. Then the data describe phenomenologically by looking at the basic principles of speech components as a reference for the analysis. From the research that has been done, the results obtained that the dialect shift that occurs in Betawi occurs in the generation of children and parents. This form of shift can be identified in the use of shifting Betawi vocabulary into other vocabularies. Other languages are dominated by Indonesian, indirectly the Betawi community's second language. At the same time, the causes of shifting dialects in the Betawi community include the influence of language variations and the lack of loyalty of the local community.